2017
DOI: 10.1177/1049909117701895
|View full text |Cite
|
Sign up to set email alerts
|

“It Has Changed My Life”: An Exploration of Caregiver Experiences in Serious Illness

Abstract: Background:Informal, unpaid caregivers shoulder much of the care burden for individuals with serious illness. As part of a project to create an innovative model of supportive care for serious illness, a series of user interviews were conducted, forming the basis for this article.Objective:To understand both individual and interpersonal aspects of caregiving for serious illness.Methods:Twelve semistructured group interviews were conducted with patients, families, and professionals as part of a larger study of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 67 publications
(94 reference statements)
1
27
0
Order By: Relevance
“…This review identified some positive aspects to providing care to the patient, which is also reflected in other literature (Anderson and White, ). Understanding the positive aspects of caring and the associated resilience and positive coping strategies may inform nurses how to effectively support families in their caring role.…”
Section: Discussionmentioning
confidence: 99%
“…This review identified some positive aspects to providing care to the patient, which is also reflected in other literature (Anderson and White, ). Understanding the positive aspects of caring and the associated resilience and positive coping strategies may inform nurses how to effectively support families in their caring role.…”
Section: Discussionmentioning
confidence: 99%
“…They can be the care recipient's family members, other relatives, friends or neighbours. Although care recipients may have different conditions, informal caregivers share many common caregiving experiences, regardless of whether the care recipient are critical care survivors (Haines, Denehy, Skinner, Warrillow, & Berney, 2015) or having chronic conditions (Anderson & White, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…If there are available carers, then they need practical, emotional, and social help and support in their caring role (Rosenberg, Horsfall, Leonard, & Noonan, 2015), with many older carers equally unwell (McKechnie, MacLeod, & Jaye, 2011). Expectations of family members in care-giving roles at the end of life are high, with overwhelming financial, emotional, and physical challenges De Korte-Verhoef et al, 2014), albeit often counterbalanced with descriptions of life altering rewards (Anderson & White, 2018). Despite this, families are increasingly expected to take on this caring role (Thomas et al, 2018).Caring can then often fail in the community, with dying taken back into hospital, due to these considerations of overwhelming family carer burden, and the economic costs of being ill (Gardiner, McDermott, & Hulme, 2017).…”
Section: Introductionmentioning
confidence: 99%